Unrests in South Africa: Causes and Effects on the Municipal Election 2021 - VORONINA Natalia Alexandrovna (Ученые записки Института Африки Российской академии наук)
November 1, 2021 saw municipal elections in South Africa, with the turnout below 50% and ANC securing a mere 45.6% compared against 64% in 2016. Referring to the pandemic, the Independent Electoral Commission of South Africa applied to the Constitutional Court to have the elections postponed till late February 2022, but failed to do so. Whereas a low turnout can be explained by the fear of pandemic, disappointing results for ANC could be accounted for by a number of reasons, including South African unrests of July 2021. The article analyzes the July unrests and their effect on the 2021 municipal elections.